Prostitution adolescente et économie domestique dans le contexte portuaire de Pucallpa (Amazonie péruvienne) - Robin Cavagnoud; Jaris Mujica (Cahiers des Amériques Latines, 2011)
The sexual exploitation of adolescents is a phenomenon that has grown with the expansion of extractive industries (timber, oil, minerals and gas) in the Peruvian Amazon. The article presents results of a long fieldwork in the city of Pucallpa and the route north of the Ucayali River. It emphasizes the mechanisms of exploitation performing local sexual trade of adolescents in restaurants, bars and sawmills around the river port. The practice of this kind of prostitution is attached to the trade of food and alcoholic beverages in spaces with important male presence. This phenomenon is not due to an organized criminal logical, but to a strategy of domestic return linked to family network and running on from an economy of care in situation of precariousness.